Application of Neural Networks in the Optimization of Francis Turbine Draft Tubes - Oliveira, Eduardo Fabian de; Silva, Raquel da Cunha Ribeiro da; Oliveira, Dhaianny Guizoni de (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2025: Anais do XXII Congresso Latino-Americano de Software Livre e Tecnologias Abertas, 2025)
This study proposes the application of artificial neural networks (ANNs) to optimize the performance of hydraulic turbines, with a specific focus on the draft tube. The research is motivated by the need to enhance energy efficiency in hydroelectric systems, in alignment with the Sustainable Development Goals. The methodology combines computational fluid dynamics (CFD) simulations and machine learning techniques, utilizing operational data from a Francis turbine. Results demonstrate the potential of ANNs to predict and improve key performance parameters, offering a novel approach to hydraulic design optimization. The integration of computational modeling and artificial intelligence emerges as a promising tool for the renewable energy sector.